Prospects for sustained harvesting of mopane (Colophospermum mopane) on the Venetia Limpopo Nature Reserve and its implications for browsing ungulates - Cunningham, Peter Low (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc) -- Stellenbosch University, 1996.